2019
DOI: 10.1038/s41467-018-08168-9
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of medial prefrontal cortex Drd1 neurons produces rapid and long-lasting antidepressant effects

Abstract: Impaired function in the medial prefrontal cortex (mPFC) contributes to depression, and the therapeutic response produced by novel rapid-acting antidepressants such as ketamine are mediated by mPFC activity. The mPFC contains multiple types of pyramidal cells, but it is unclear whether a particular subtype mediates the rapid antidepressant actions of ketamine. Here we tested two major subtypes, Drd1 and Drd2 dopamine receptor expressing pyramidal neurons and found that activating Drd1 expressing pyramidal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 54 publications
13
106
1
Order By: Relevance
“…Number 3 March 2020 amygdala, which is necessary and sufficient for the rapid and long-lasting antidepressant actions of ketamine (19,21). Because behavioral tests were conducted 24 hours after dosing to avoid the acute side effects of ketamine, we also acknowledge the possibility that there could be adaptations that require GluN2B on GABA interneurons that mediate the actions of ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Number 3 March 2020 amygdala, which is necessary and sufficient for the rapid and long-lasting antidepressant actions of ketamine (19,21). Because behavioral tests were conducted 24 hours after dosing to avoid the acute side effects of ketamine, we also acknowledge the possibility that there could be adaptations that require GluN2B on GABA interneurons that mediate the actions of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous postsynaptic currents were determined before and during bath application of ketamine at 1 μM, the estimated concentration reached in the human brain after i.v. infusion of a dose in the therapeutic range (18) and a concentration that blocks approximately 50% of NMDA-induced currents (19); or 10 μM, a concentration that is sufficient to block approximately 80% of NMDA-induced currents (20). These concentrations have also been used in recent reports (4,13).…”
Section: Gaba Interneurons Are the Cellular Trigger For Ketamine's Ramentioning
confidence: 99%
“…At the end of the experiment, the enhancement of neuronal activity was further validated by observing increased c-fos expression in mCherry + neurons (Figure 5m). In addition to these results, a recently published study showed that optogenetic activation of Drd1 + mPFC neurons decreases immobility time in the forced swim test, suggesting the possibility that these Drd1-expressing neurons may regulate general aversive or active coping responses 60 . Altogether, our data demonstrate that activating DAsensing mPFC neurons is sufficient to rescue escape behavior after aversive learning.…”
Section: Closed Loop Interactions Between Vta and Mpfc In Aversive Lementioning
confidence: 64%
“…Ketamine’s action on receptors other than the NMDAR, could also contribute to the observed effects. Recent findings indicate that activation of dopamine D1 receptors on pyramidal cells in the prefrontal cortex and/or the action of a metabolite of ketamine on α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors might contribute to its long-lasting antidepressant effects (57) (58). However, ketamine’s affinities at other receptors (range of Ki values= 19-131μM) are considerably lower than its affinity for the NMDAR, and it is not clear if ketamine exhibits significant striatal dopamine receptor occupancy in vivo at behaviourally relevant doses (59, 60).…”
Section: Discussionmentioning
confidence: 99%